Reduced CO2/O2 specificity of ribulose-bisphosphate carboxylase/oxygenase in a temperature-sensitive chloroplast mutant of Chlamydomonas. - Chen, Z X (1988)
The Chlamydomonas reinhardtii chloroplast mutant 68-4PP is phenotypically indistinguishable from wild type at 25 degrees C but fails to grow photosynthetically at 35 degrees C. It had about 30% of the wild-type level of ribulose-1,5-bisphosphate carboxylase/oxygenase (EC 4.1.1.39) holoenzyme and carboxylase activity when grown at 25 degrees C, but less than 15% when grown at 35 degrees C. Pulse-labeling with 35S showed that the decrease in enzyme level at the restrictive temperature was not a result of reduced synthesis of enzyme subunits. The CO2/O2 specificity factor (VCKO/VOKC, where VC and VO are Vmax values for carboxylation and oxygenation and KC and KO are Km values for CO2 and O2) of the mutant enzyme was found to be significantly less than that of the wild-type enzyme (54 +/- 2 and 62 +/- 1, respectively), and this alteration was accompanied by increases in KO and KC and a decrease in VC/VO. DNA sequencing revealed a single missense mutation in the 68-4PP chloroplast large-subunit gene. This mutation causes leucine to be replaced by phenylalanine at position 290 in the large-subunit polypeptide sequence. These results (i) support previous studies that implicated this region of the large subunit as an important structural component of the enzyme's function and (ii) demonstrate that chloroplast genetic modification of the CO2/O2 specificity factor of a plant-type carboxylase/oxygenase is feasible.